Biological Matrix for 2.5D Renal Model in vitro - Lacueva Aparicio, Alodia; Fernández, Luis; Giménez, Ignacio (Jornada de Jóvenes Investigadores del I3A, 2020)
The extracellular matrix provides mechanical support to renal cells and enhance tridimensional disposition in cell culture. For that reason, biological matrices are widely used in renal models in vitro. Here we present a user-friendly 2.5D renal model that can be used for nephrotoxic assays.